PENGARUH MANAJEMEN LABA PADA HARGA EKSEKUSI ESOP DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Wikrami, Ida Ayu Ganetri Priyadarshini; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2016)
This study has the purpose to test that before stock option announcement, manager did earning management with income decreasing pattern, so that the exercise price of ESOP would be low, and to get the statistic evidence that earning management on the exercise price of stock option is influenced by good corporate governance’s moderation. There are 49 companies adopted stock option plan program during 1999-2012. Based on that amount, 33 companies was picked as sample in purposive sampling method. Moderated regression analysis (MRA) was used as data analysis technique. The analysis showed that earning management has an effect and significant on stock option’s exercise price and earning management on the exercise price of stock option is not influenced by good corporate governance’s moderation.
Keywords: income decreasing, ESOP, exercise price, good corporate governance